(untitled) (World Bulletin of Social Sciences, 2024)
This article describes the brief history of Afghan immigrants who lived in Turkestan. Samarkand region of Turkestan governorate was selected as the main object of the research. As a result of the active occupation policy of the Russian Empire, after the land of Turkestan was occupied as a result of military superiority, an active foreign policy was conducted through the Governor General. In this process, the existing historical relations of the peoples of the country with the neighboring countries, first of all, Afghanistan, were used with advantage. In addition, the article analyzes the political, socioeconomic activities of Afghan citizens who lived in Samarkand in the late 19th - early 20th centuries. It is known that in world politics of the 19th century, economic development and active colonial policy are considered as a developed period. In this study, the essence of the foreign policy of the Afghan tribal chiefs, who served as a tool in the foreign policy of the Russian and British empires of the Afghans in the territory of Samarkand region, and the foreign policy of the empires with their participation is shown.